2008
DOI: 10.4257/oeco.2008.1201.02
|View full text |Cite
|
Sign up to set email alerts
|

As Rotas De Liberação Do Carbono Dos Detritos De Macrófitas Aquáticas

Abstract: RESUMONesse estudo discutem-se eventos relativos à liberação do carbono (e.x. CO 2 , CH 4 , COD) durante a decomposição das macrófi tas aquáticas. Foi realizada uma breve compilação para examinar a variação dos teores de carbono dessas plantas. Os processos de mineralização são discutidos em função de fatores controladores dos sistemas aquáticos continentais (ex. temperatura, disponibilidade de oxigênio dissolvido). Propõe-se ainda, um modelo cinético que descreve e compara as velocidades dos processos de mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…As they presented slower decomposition rates, the fibers are generally accumulated in limnic sediments, becoming possible precursors of humic compounds (Bianchini and Cunha-Santino, 2008), which allows us to affirm that the refractory fractions of E. densa and C. braunii, could act in the ecosystem metabolism as a possible precursor source in the humic substances genesis, due to the low coefficient of mineralization (k R ). The dissolved carbon presented a refractory potential during E. densa and C. braunii decomposition, with low mineralization coefficients (K 3 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As they presented slower decomposition rates, the fibers are generally accumulated in limnic sediments, becoming possible precursors of humic compounds (Bianchini and Cunha-Santino, 2008), which allows us to affirm that the refractory fractions of E. densa and C. braunii, could act in the ecosystem metabolism as a possible precursor source in the humic substances genesis, due to the low coefficient of mineralization (k R ). The dissolved carbon presented a refractory potential during E. densa and C. braunii decomposition, with low mineralization coefficients (K 3 ).…”
Section: Discussionmentioning
confidence: 98%
“…During the biomass decomposition of submerged macrophytes, significant changes can occur in water, that is, increase of dissolved and particulate organic matter, aquatic system acidification, increased electrical conductivity (Bianchini and Cunha-Santino, 2010) and nutrient release (Wang and Fan, 2013). Such physical and chemical changes may be affected either by extrinsic factors like intrinsic ones, such as the species chemical composition (Bianchini and Cunha-Santino, 2008) and the nutrient concentration in the water which can accelerate the organic matter degradation or make it slower (Xie et al, 2004) due to the heterotrophic activity dynamics during the degradation process.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon from aquatic macrophytes and periphyton, for example, can vary in quantity and quality according to the present species (Osborne et al, 2007). The mineralized or humified fractions and the velocity of mineralization and humification can also vary (Bianchini Junior and Cunha-Santino, 2008). Besides different sources, DOM is also influenced by various mechanisms, such as water mixing and photodegradation (Zhang et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…However, Daniel et al (21) showed that in the absence of recent algal carbon the microbial loop keeps transferring energy to metazooplankton. Regarding the carbon from aquatic macrophytes decomposition, it is estimated that around 24% can be converted to microorganisms’ biomass (10). These pieces of information lead to the importance of carbon quality determining microbial loop role in an ecosystem.…”
Section: Introductionmentioning
confidence: 99%